Face Detection and the Development of Own‐Species Bias in Infant Macaques. Issue 1 (25th May 2016) - Simpson, Elizabeth A.; Jakobsen, Krisztina V.; Damon, Fabrice; Suomi, Stephen J.; Ferrari, Pier F.; Paukner, Annika
Abstract : In visually complex environments, numerous items compete for attention. Infants may exhibit attentional efficiency—privileged detection, attention capture, and holding—for face‐like stimuli. However, it remains unknown when these biases develop and what role, if any, experience plays in this emerging skill. Here, nursery‐reared infant macaques' ( Macaca mulatta ; n  = 10) attention to faces in 10‐item arrays of nonfaces was measured using eye tracking. With limited face experience, 3‐week‐old monkeys were more likely to detect faces and looked longer at faces compared to nonfaces, suggesting a robust face detection system. By 3 months, after peer exposure, infants looked faster to conspecific faces but not heterospecific faces, suggesting an own‐species bias in face attention capture, consistent with perceptual attunement.